(untitled) (Interdisciplinary Studies Journal, 2025)
The relationship between society and space is essential for individual development, as everyday experiences create emotional bonds and memories with places. This project aims to develop teaching practices in the Geography discipline, considering the multicultural reality of students enrolled in technical courses integrated with high school at IFRS – Rio Grande Campus/RS. The proposal connects the subject’s content to the students’ family and community contexts, renewing geographic knowledge. Methodologically, it is based on the concepts of geographic space, landscape, territory, region, and place. Through photographic records, interviews, and audiovisual productions, students share everyday experiences and bonds, advancing a (de)colonial territorial analysis. Thus, their trajectories become community narratives that enrich geographic science and knowledge production through exhibitions, lectures, and workshops. By valuing the mediation between theory and practice with images and narratives, the project uses students’ work to construct new (geo)graphies, addressing multiple experiences and cultural practices. In this way, it connects the trajectories of popular groups to education, promoting the understanding of a diverse and plural society.